2017
DOI: 10.3892/mmr.2017.6402
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of oleanolic acid on oxidative stress and the expression of cytokines and collagen by the AKT/NF-κB pathway in silicotic rats

Abstract: Oleanolic acid (OA), a natural pentacyclic triterpenoid, has been reported to have several benefits and medicinal properties. However, its protective effects against silica‑induced lung injury and fibrosis remain to be elucidated. The aim of the present study was to investigate the effects of OA on oxidative stress, and the expression of cytokines and collagen in silicotic rats. Male rats were induced by intratracheal instillation of silicosis (250 mg/kg), with the exception of the control group (NS). The rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…Several studies have shown that oxidative stress can decrease the expression of several survival signaling molecules, including PI3K, p-AKT and Bcl-2. PI3K pathway activation is involved in cell proliferation and cell survival in response to cytokines and growth factors (34)(35)(36). In the present study, it was found that the ratio of p-AKT/AKT was decreased following stimulation with cholesterol, indicating that the PI3K/AKT signaling pathway was inhibited by stimulation of cholesterol.…”
Section: Discussionsupporting
confidence: 46%
“…Several studies have shown that oxidative stress can decrease the expression of several survival signaling molecules, including PI3K, p-AKT and Bcl-2. PI3K pathway activation is involved in cell proliferation and cell survival in response to cytokines and growth factors (34)(35)(36). In the present study, it was found that the ratio of p-AKT/AKT was decreased following stimulation with cholesterol, indicating that the PI3K/AKT signaling pathway was inhibited by stimulation of cholesterol.…”
Section: Discussionsupporting
confidence: 46%
“…Several recent studies investigated the antioxidant activity of OA in different disease models. For example, OA was found to reduce oxidative stress in silicotic rats by modulating the Akt/NF-κB pathway [32]. Moreover, OA suppressed oxidative stress by regulating the stanniocalcin-1 pathway in a cell model of Alzheimer's disease treatment [33], as well as repressed oxidative stress via the SIRT3/NF-κB axis in an in vitro osteoarthritis cell model [34].…”
Section: Discussionmentioning
confidence: 99%
“…Silicosis is an irreversible chronic disease that continues to deteriorate. The treatment is based on the principle of avoiding complications as far as possible and needs long-term medication, and the quality of life of patients will be seriously affected with the development of the disease (5). The silicotic lung has the characteristics of high medical costs, high disability rate and high mortality rate, heavy financial burden and psychological pressure on the patient's family, and no special drugs have been developed for the treatment of silicosis so far, therefore, the treatment can only be the basis of controlling and delaying the development of the disease, and the main purpose is to improve the immune function and quality of life of patients at the same time (6).…”
Section: Introductionmentioning
confidence: 99%